Laboratory friction measurements of high-grade minerals - Matt J Ikari; Åke Fagereng (PANGAEA, 2020)
Here, we present the results of laboratory shearing experiments on chlorite schist, epidotite, and a hornblende-dominated amphibolite, and mixtures of these rocks, and evaluate their frictional properties and microstructures.